KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS X OTKP SMK NEGERI 1 MUARA BUNGO KABUPATEN BUNGO - SU BAGYO (LP3M STKIP Muhammadiyah Muara Bungo, 2020)
“Ability to write Procedure Text of SMK Negeri 1 Muara Bungo”. Classroom Action Research (PTK). Subjects of Indonesian Language, this study aims to: (1) describe the ability to write procedural text for class X students, (2) describe the ability to write procedural text for class X students on the aspect of content; (3) to describe the students' ability to write procedural text for class X on the structural aspects; (4) to describe the students' ability to write procedural text for class X on the aspects of writing rules; (5) to describe the students' ability to write procedural text for class X on aspects of linguistic characteristics. This type of quantitative descriptive research is research that produces numbers to measure the ability to write procedural texts for class X OTKP students of SMK Negeri 1 Muara Bungo. The results showed that the class X OTKP students of SMK Negeri 1 Muara Bungo obtained an average score of 80.54 with a percentage of 77.41%, which was able to write procedural texts. In the content aspect, the average score of the sample students was in the capable category with a value of 86.29. In the structural aspect, the mean score of high school students is in the capable category with a score of 85.48. In the aspect of writing rules, the average score of the sample students was in the sufficient category with a value of 73.79, and in the aspect of linguistic characteristics, the average score of the sample students was in the sufficient category with a value of 77.01.